Initial Complete Chloroplast Genomes of Alchemilla (Rosaceae): Comparative Analysis and Phylogenetic Relationships - Rono, Peninah Cheptoo; Dong, Xiang; Yang, Jia-Xin; Mutie, Fredrick Munyao; Oulo, Millicent A.; Malombe, Itambo; Kirika, Paul M.; Hu, Guang-Wan; Wang, Qing-Feng (Frontiers in Genetics, 2020)
The genus Alchemilla L., known for its medicinal and ornamental value, is widely distributed in the Holarctic regions with a few species found in Asia and Africa. Delimitation of species within Alchemilla is difficult due to hybridization, autonomous apomixes, and polyploidy, necessitating efficient molecular-based characterization. Herein, we report the initial complete chloroplast (cp) genomes of Alchemilla. The cp genomes of two African (Afromilla) species Alchemilla pedata and Alchemilla argyrophylla were sequenced, and phylogenetic and comparative analyses were conducted in the family Rosaceae. The cp genomes mapped a typical circular quadripartite structure of lengths 152,438 and 152,427 base pairs (bp) in A. pedata and A. argyrophylla, respectively. Alchemilla cp genomes were composed of a pair of inverted repeat regions (IRa/IRb) of length 25,923 and 25,915 bp, separating the small single copy (SSC) region of 17,980 and 17,981 bp and a large single copy (LSC) region of 82,612 and 82,616 bp in A. pedata and A. argyrophylla, respectively. The cp genomes encoded 114 unique genes including 88 protein-coding genes, 37 transfer RNA (tRNA) genes, and 4 ribosomal RNA (rRNA) genes. Additionally, 88 and 95 simple sequence repeats (SSRs) and 37 and 40 tandem repeats were identified in A. pedata and A. argyrophylla, respectively. Significantly, the loss of group II intron in atpF gene in Alchemilla species was detected. Phylogenetic analysis based on 26 whole cp genome sequences and 78 protein-coding gene sequences of 27 Rosaceae species revealed a monophyletic clustering of Alchemilla nested within subfamily Rosoideae. Based on a protein-coding region, negative selective pressure (Ka/Ks < 1) was detected with an average Ka/Ks value of 0.1322 in A. argyrophylla and 0.1418 in A. pedata. The availability of complete cp genome in the genus Alchemilla will contribute to species delineation and further phylogenetic and evolutionary studies in the family Rosaceae.